Specifications for Nitrometer, General Assembly of Parts (Standard Laboratory Apparatus Adopted by the Manufacturing Chemists Association of the United States Part 1, 1922)
From Manufacturing Chemists' Association Catalog for Standard Laboratory Apparatus, Part 1. Nitrometer, general assembly of parts.
Keywords: Scientific apparatus and instruments; Laboratories--Equipment and supplies; Manufacturing Chemists' Association (U.S.); Chemical apparatus